Histomorphological Study of The Spectrum of Prostatic Lesions in Surgical Biopsy Specimens - K, Srikanth; Gandhi, N; Vimal, Mourouguessine; Ivan, Erli Amel (Annals of Pathology and Laboratory Medicine, 2019)
Background: Prostatism is one of the commonest health concerns in geriatric population with significant morbidity and mortality. The incidence of it increases with age. Histopathological evaluation plays a major role in the diagnosis and management of Prostate lesions. Aims and Objectives: To study the spectrum of prostate specimens encountered by the pathologists and to categorize them based on their histomorphological features and to correlate it with the clinical and other laboratory parameters. Material and methods: Hematoxylin and Eosin sections of 100 prostatic biopsies received in the department of Pathology of a tertiary care centre over a period of 18 months were studied. Relevant clinical and laboratory data were collected. Results: Out of 100 prostatic biopsies studied, 91 were TURP and 9 were core biopsies. Prostatic lesions was common in the age group of 61-70 years. 75% of cases were benign with or without prostatitis, 15% malignant and 10% cases were pre malignant. 25% cases were found to have associated prostatitis with the benign and malignant lesions. The most common microscopic feature in benign cases was fibromuscular hyperplasia. Conclusion: The present study shows that benign lesions are more common than the malignant ones. Among benign lesions, BPH was the most common entity. The most common age group affected was 7th decade.